Ethical Recommendations for Managing the Affective-Sexual Dimension in People with Disabilities (Revista Iberoamericana de Bioética, 2021)
The acknowledgement of the rights of persons with disabilities and the development of a comprehensive framework of care have been two great milestones of the last decades. However, and in spite of these clear advances, the affective-sexual dimension continues to present difficulties, both with regard to its recognition and the approach taken. This ethical reflection and creation of ethical recommendations seeks to offer a general perspective to professionals, helping them to identify their own values, to recognize the values of the people aided, to promote dialogue and discussion, as well as to identify and spread awareness of possible situations of risk, thereby promoting attitudes based on respect.
Keywords: disability; sexuality; decision-making; competence